Gene Expression of pelA and pslA in Pseudomonas Aeruginosa under Gentamicin Stress - AL-Sheikhly, Mahmood Abdul Razzaq Hassan; Musleh, Laith N.; Al-Mathkhury, Harith J. F. (Iraqi Journal of Science, 2020)
Pseudomonas aeruginosa produces an extracellular bioï¬lm matrix that consists of nucleic acids, exopolysaccharides, lipid vesicles, and proteins. Alginate, Psl and Pel are three exopolysaccharides that constitute the main components in biofilm matrix, with many biological functions attributed to them, especially concerning the protection of the bacterial cell from antimicrobial agents and immune responses. A total of 25 gentamicin-resistant P. aeruginosa selected isolates were enrolled in this study. Biofilm development was observed in 96% of the isolates. In addition, the present results clarified the presence of pelA and pslA in all the studied isolates. The expression of these genes was very low. Even though all biofilms were affected by gentamicin, the results of fold change showed a wide variation. In conclusion, all P. aeruginosa isolates carried psl and pel regardless of the intensity of the biofilm. A strongly positive correlation with gentamicin minimum inhibitory concentration was noticed.